The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1016/s0006-3495(01)76202-9
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Entrapment of Polynucleotides upon Electrostatic Interaction with Ethanol-Destabilized Cationic Liposomes

Abstract: This study describes the effect of ethanol and the presence of poly(ethylene) glycol (PEG) lipids on the interaction of nucleotide-based polyelectrolytes with cationic liposomes. It is shown that preformed large unilamellar vesicles (LUVs) containing a cationic lipid and a PEG coating can be induced to entrap polynucleotides such as antisense oligonucleotides and plasmid DNA in the presence of ethanol. The interaction of the cationic liposomes with the polynucleotides leads to the formation of multilamellar li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
146
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(149 citation statements)
references
References 53 publications
3
146
0
Order By: Relevance
“…The resulting cationic liposomes were 60 nm in diameter and exhibited a zeta potential of ~40 mV. As previously reported, 15,25 size was found to increase slightly on complexation with siRNA molecules and zeta potentials also decreased accordingly. Particle size showed a maximum at N/P ratio of 5.…”
Section: Preparation and Characterization Of Lipoplexes And Lnpssupporting
confidence: 81%
See 1 more Smart Citation
“…The resulting cationic liposomes were 60 nm in diameter and exhibited a zeta potential of ~40 mV. As previously reported, 15,25 size was found to increase slightly on complexation with siRNA molecules and zeta potentials also decreased accordingly. Particle size showed a maximum at N/P ratio of 5.…”
Section: Preparation and Characterization Of Lipoplexes And Lnpssupporting
confidence: 81%
“…15,25 Cationic liposomes were composed of the following lipids: DODMA, PEG-DSPE, DSPC and cholesterol in a molar ratio of 50:1.5:10:38.5. Lipids were dissolved in 3 mL ethanol and then 70.5 µL 1N HCl and 6.93 mL distilled water were added to this mixture (total lipids: 7.8 mg/mL).…”
Section: Preparation Of Lipoplexesmentioning
confidence: 99%
“…MLP/siRNA complexes were made as previously reported. 10,35,37 As shown in Figure 2A, we found that MLP had strong ability to bind siRNA, which completely complexed siRNA at an N/P ratio of 5:1 (the molar ratio of nitrogen in MLP to phosphate in siRNA) through electrostatic interaction, leading to no free siRNA in the gel. The control liposome (DLP) was prepared by PD, DSPE-PEG2000, and cholesterol, and was mixed with siRNA in pH=3 citrate buffer at the optimal N/P ratio of 5:1 ( Figure S2).…”
Section: Results and Discussion Synthesis And Physiochemical Propertimentioning
confidence: 76%
“…Construction of siRNA-encapsulated Liposomes-siRNAencapsulated liposomes, called stable nucleic acid lipid particles (SNALPs), were prepared according to a method reported previously (25). 1,2-dioleyloxy-3-(dimethylamino)propane, 1,2-dioctadecanoyl-sn-glycero-3-phosphocholine, cholesterol (2,15-dimethyl-14-(1,5-dimethylhexyl)tetracyclo-heptadec-7-en-5-ol), and PEG2000PE (1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N-[methoxy(polyethylene glycol)-2000]) were purchased from Avanti Polar Lipids Inc. (Alabaster, AL) and dissolved in ethanol at a molar ratio of 40:10:47:3.…”
Section: Methodsmentioning
confidence: 99%